Analysis of the Fraud Triangle in Detecting Financial Statement Fraud - Sipatuhar, Elisabhet; Wahyudi, Ilham; Wijaya, Rico (Faculty of Economics and Business Universitas Jambi, 2024)
This study aims to examine and analyze the influence of financial stability, external pressure, financial targets, nature of industry, and rationalization on financial statement fraud. The research population comprises state-owned enterprises (BUMN) listed on the Indonesia Stock Exchange (IDX) for the period 2014–2018. A purposive sampling technique was applied, resulting in a final sample of 12 companies. Data were analyzed using logistic regression with SPSS software. The empirical findings reveal that financial stability and the nature of the industry have a significant effect on the detection of financial statement fraud. In contrast, external pressure, financial targets, and changes in auditors do not show a significant impact on fraudulent financial reporting. This study contributes to the literature on forensic accounting and fraud detection by highlighting key financial and contextual indicators that can serve as early warning signs for financial misreporting. The results also provide practical implications for auditors, regulators, and corporate governance bodies to strengthen fraud risk assessments in state-owned enterprises.